Multitemporal analysis of total coliforms and Escherichia Coli in the upper basin of the Bogotá river (2007–2017) (2020)
The Bogotá River, located in the department of Cundinamarca, is the main fluvial channel in the savanna near the Colombian Capital District of Bogotá. This study sought to assess factors associated with this water source, where pollution stems from human activities performed at the upper basin and along the river, through the measurement of pollution microbiological indicators, such as the total coliforms and Escherichia coli groups. For the said purpose, a descriptive qualitative research methodology was implemented. To this end, a multitemporal analysis of these indicators was performed across 32 stations comprising this basin’s monitoring network. Samples were assessed through defined substrate technology by the Autonomous Regional Corporation of Cundinamarca, which also provided annual rainy and dry season data for 2007–2017. According to icrobiological quality analysis conducted in the upper basin of the Bogotá River, the concentration of total coliforms and Escherichia coli has increased as a result of domestic and agricultural wastewater discharges, thus unearthing the existent shortcomings in the wastewater treatment systems implemented in these municipalities and causing negative effects on the population and ecosystem. A major constraint was the lack of data from La Floresta station. This article is aimed at disclosing the current condition of the upper basin of the Bogotá River and discussing the control measures related to the right to water that must be exercised by the governmental bodies and the Colombian Government itself.